Determination of the Scattered Radiation at the Neutron Calibration Laboratory of IPEN using the Shadow Cone Method (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Because of the increase in the demand for the calibration of neutron detectors, there is a need for new calibration      services. In this context, the Calibration Laboratory of Instituto de Pesquisas Energéticas e Nucleares (IPEN), São Paulo, which already offers calibration services of radiation detectors with standard X, gamma, beta and alpha beams, has recently projected a new test laboratory for neutron detectors. This work evaluated the contribution of dispersed neutron radiation in this laboratory, using the Cone Shadow Method and a Bonner Sphere Spectrometer to take the measurements at a distance of 100 cm from the neutron source. The dosimetric quantities Ambient Dose Equivalent Rate (Ḣ*(10)) and Ambient Dose Equivalent Conversion Coefficient (h*(10)) were obtained at the laboratory, allowing the calibration of detectors.